The Impact of Climate Change on Human Health in Bibliometric Analysis - Loso Judijanto; Sulistyo Andarmoyo; Muhamad Ammar Muhtadi (Westscience Press, 2024)
This bibliometric analysis offers a comprehensive examination of the scholarly literature concerning the impact of climate change on human health. With a focus on papers published from 1993 to 2024, the study employs systematic search strategies and analytical techniques to identify key themes, publication trends, and gaps in research. The findings reveal a substantial body of literature, comprising 980 papers with over 354,000 citations, indicative of the significant attention this topic has received from researchers. The analysis highlights prominent research themes, including the direct and indirect health impacts of climate change, socioeconomic disparities, agricultural and ecological consequences, and the intersection with infectious diseases such as COVID-19. Through critical appraisal and synthesis of findings, the study underscores the importance of continued research efforts to inform evidence-based policies and interventions aimed at addressing the complex health challenges posed by climate change.